A Rare Complication of the Treatment of Simple Renal Cysts: Nephrostomy Catheter Breakage after Alcohol Treatment and Laparoscopic Management - Barbaros Başeskioğlu; Ali Ülgen (Journal of Urological Surgery, 2016)
The prevalence of simple renal cysts increases with age. Simple renal cyst aspiration and sclerotherapy with percutaneous nephrostomy catheter is frequently used in urological practice. This method can be applied under local anesthesia and various complications of this method have been reported. In this paper, we report an unusual complication of this method; the distal part of the nephrostomy catheter had separated after renal cyst aspiration and laparoscopic procedure was used to remove the end part of the catheter which remained within the cyst wall in the pararenal area.